Incidence and Severity of Cowpea Rust Disease among Selected Cowpea Genotypes in Northern Ghana (Ghana Journal of Science, Technology and Development, 2023)
Rust infections interfere with root development and nutrient uptake as well as photosynthetic processes in cowpea plants and can cause up to about 40 % yield losses in susceptible genotypes. This study seeks to evaluate the incidence and severity of cowpea rust disease among some selected cowpea genotypes and also to determine the impact of the disease on yield. Six (6) cowpea genotypes were assessed for resistance to the rust disease under natural field conditions. The experiment was laid out in Randomized Complete Block Design with three replications at Nyankpala, Tolon District of northern Ghana during the 2021 cropping season. Rust disease intensities and yield data were measured. Results revealed that four genotypes; IT07K-303-1, IT10K-1070-2, IT10K-837-1, and IT14K-1424-12 were highly resistant to disease. SARI-2-50-80 was susceptible to the disease, whilst SARI-3-11-100 was observed to be highly susceptible to the disease. Disease incidence and severity had a significant negative association with pod yield and grain yield. Variations in the resistance among cowpea genotypes as identified in this study will serve as an important information for future breeding interventions against the disease.